Clarifying sub-genomic positions of QTLs for flowering habit and fruit quality in U.S. strawberry (Fragaria×ananassa) breeding populations using pedigree-based QTL analysis. (8th November 2017) - Verma, Sujeet; Zurn, Jason D; Salinas, Natalia; Mathey, Megan M; Denoyes, Beatrice; Hancock, James F; Finn, Chad E; Bassil, Nahla V; Whitaker, Vance M
Abstract: The cultivated strawberry ( Fragaria × ananassa ) is consumed worldwide for its flavor and nutritional benefits. Genetic analysis of commercially important traits in strawberry are important for the development of breeding methods and tools for this species. Although several quantitative trait loci (QTL) have been previously detected for fruit quality and flowering traits using low-density genetic maps, clarity on the sub-genomic locations of these QTLs was missing. Recent discoveries in allo-octoploid strawberry genomics led to the development of the IStraw90 single-nucleotide polymorphism (SNP) array, enabling high-density genetic maps and finer resolution QTL analysis. In this study, breeder-specified traits were evaluated in the Eastern (Michigan) and Western (Oregon) United States for a common set of breeding populations during 2 years. Several QTLs were validated for soluble solids content (SSC), fruit weight (FWT), pH and titratable acidity (TA) using a pedigree-based QTL analysis approach. For fruit quality, a QTL for SSC on linkage group (LG) 6A, a QTL for FWT on LG 2BII, a QTL for pH on LG 4CII and two QTLs for TA on LGs 2A and 5B were detected. In addition, a large-effect QTL for flowering was detected at the distal end of LG 4A, coinciding with the FaPFRU locus. Marker haplotype analysis in the FaPFRU region indicated that the homozygous recessive genotype was highly predictive of seasonal flowering. SNP probes in the FaPFRU region may help facilitate marker-assisted selection for this trait. Abstract : Strawberry breeding: Finessing flowering time and fruit quality A new genetic approach improves fine-resolution mapping of strawberry genes, promoting perpetual flowering and high fruit quality. Many economically important traits in strawberries are controlled by 'quantitative trait loci' (QTLs), sections of DNA showing statistical correlations with variation in measurable traits such as size or sugar content. An international team led by Nahla Bassil at the USDA-ARS National Clonal Germplasm Repository in Oregon, USA, developed powerful new tools to identify variable DNA sites and map the position of QTLs. Numerous QTLs were recognized and located more precisely than before, including four for different aspects of fruit quality, and one with an important effect upon flowering time. The results will enable breeders to predict the flowering habit of strawberry plants using a simple DNA test, and will further the development of everbearing varieties of strawberry.